Analysis of Local Economic Potential and Competitiveness Economic Sector in Improving Local Economic Development (Study in Batu City) - Anggraeny Puspaningtyas (Jurnal Administrasi Publik, 2013)
Abstract: Analysis of Local Economic Potential and Competitiveness Economic Sector in Improving Local Economic Development. Batu as the youngest autonomy region in East Java, is one of the city that formed in 2001 as a breakaway from Malang Regency. Since 2006-2010 Batuis a city which has faster economic growth compared to East Java and its PDRB per capita is lower than the average of PDRB per capita of East Java. Moreover, from this point of view, the researcher aims to analyze the best sector (superior potential) and competitive potency of Batu which able to support its economic development.The purpose of this study is to analyze and describe the superior potential and competitiveness sector in 2007-2010 period and the contribution of superior sector to PAD Batu City. This study uses qualitative and quantitative approach. After using quantitative approach, the researcher will continue the analysis using qualitative approach as a supporting method for the previous one. For quantitative analysis, the researcher uses analytical tools such as Location Quotient (LQ) and Shift Share (SS) method. For qualitative analysis, the researcher use descriptive qualitative approach. The results of this study areBatu has three superior sector during 2007-2010, there are services sector; trade, hotel and restaurant sector; and agriculture sector. The competitiveness sector are trade, hotel and restaurant sector; services sector and construction sector. The superior sector that contributed to PAD are services, hotel and restaurant sector. Agriculture sector since 2007-2011 not became competitiveness sector and indirectly has contribution to PAD. The suggestions to develop agriculture sector which begins to drop its production and empowerthe people who work in each sectors especially in agriculture. Keywords: LQSS, Potential Sector, Competitiveness Sector, PAD Abstrak: Analisis Potensi Ekonomi Daerah dan Sektor Ekonomi yang Berdaya Saing dalam Meningkatkan Pembangunan Ekonomi Daerah. Batu sebagai daerah otonomi termuda di Jawa Timur, merupakan salah satu kota yang dibentuk pada tahun 2001 sebagai pecahan dari Kabupaten Malang. Sejak2006-2010 Batu adalah sebuah kota yang memiliki pertumbuhan ekonomi yang lebih cepat dibandingkan dengan Jawa Timur dan PDRB perkapitanya lebih rendah dari rata-rata PDRB perkapita Jawa Timur. Selain itu, dari sudut pandang ini, peneliti bertujuan untuk menganalisis sektor terbaik (potensi unggulan) dan potensi yang berdaya saing di Kota Batu yang dapat mendukung tujuan pembangunan. Tujuan dari penelitian ini adalah untuk menganalisis dan menggambarkan potensi unggulan dan daya saing dalam sektor periode 2007-2010 dan kontribusi sektor unggulan terhadap PAD Kota Batu. Penelitian ini menggunakan pendekatan kualitatif dan kuantitatif. Setelah menggunakan pendekatan kuantitatif, penelitiakan melanjutkan analisis dengan menggunakan pendekatan kualitatif sebagai metode pendukung yang sebelumnya.Untuk analisis kuantitatif, peneliti menggunakan alat analisis dengan metode Location Quotient (LQ) dan Shift Share (SS). Untuk analisis kualitatif, peneliti menggunakan pendekatan kualitatif deskriptif. Hasil penelitian ini, Batu memiliki tiga sektor unggulan selama 2007-2010, yaitu sektor jasa-jasa; sektor perdagangan, hotel dan restoran; dan pertanian. Sektor yang berdaya saing adalah sektor perdagangan, hotel dan restoran; sektor jasa dan sektor bangunan/konstruksi. Sektor unggulan yang memberikan kontribusi terhadap PAD adalah jasa-jasa, hotel dan sektor restoran. Sektor pertanian sejak 2007-2011 tidak menjadi sektor daya saing dan secara tidak langsung memiliki kontribusi terhadap PAD. Saran untuk mengembangkan sektor pertanian yang mulai turun produksinya dan orang-orang yang bekerja di setiap sektor terutama di bidang pertanian. Kata Kunci: LQSS, Sektor Ungulan, Sektor yang Berdaya Saing, PAD